Dead ringer [videorecording (DVD)] - Davis, Bette, 1908-1989; Malden, Karl; Lawford, Peter, 1923-1984 (Archive collection., 2004)
Davis plays estranged twin sisters, Edith who has no money and widow Margaret who has fabulous wealth because she married the man she stole from her sister. When Edith kills Margaret she finds it harder than expected to step into her sisters' life and maintain her masquerade.